1997
DOI: 10.4141/p96-145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated and flea beetle injury to cotyledons on growth of drought-stressed oilseed rape, Brassica napus L.

Abstract: Nowatzki, T. M. and Weiss, M. J. 1997. Effects of simulated and flea beetle injury to cotyledons on growth of droughtstressed oilseed rape, Brassica napus L. Can. J. Plant Sci. 77: 475-481. Simulated injury was compared with flea beetle injury on cotyledons of oilseed rape grown at various soil moistures to determine the effects of injury on seedling growth in the greenhouse. The cotyledons of 7-d-old seedlings were injured at 0, 25, 50, and 75% of the total area with a 0.5-mm mechanical pencil or by flea beet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The majority of these studies reported detrimental effects on components of plant fitness, such as reduced shoot and root biomass (Knapp 1986;Quinn and Hall 1996;Wirf 2006), decreased flower, fruit, or seed production (Obeso 1993;Domínguez and Dirzo 1994;Koptur et al 1996;Genter et al 1997), and decreased seed size (Sackston 1959;Rockwood 1973;Koptur et al 1996). On the other hand, some studies have demonstrated compensatory or even beneficial, overcompensatory effects of herbivory (McNaughton 1983;Karban and Myers 1989;Paige 1994;Lennartsson et al 1998;Marshall et al 2005; but see Belsky 1986 andBelsky et al 1993) or variable effects, depending on whether defoliation occurred naturally or was achieved artificially (Gedge and Maun 1992;Nowatzki and Weiss 1997). For example, in wild radish, Raphanus raphanistrum, artificial clipping of leaves by scissors resulted in only minimal induced plant resistance (e.g., increased production of defensive chemicals) (Agrawal 1999(Agrawal , 2000a, whereas strong induced resistance, no induced resistance, or even induced susceptibility to herbivory occurred following attack by four lepidopteran herbivores (Agrawal 2000b).…”
Section: Introductionmentioning
confidence: 94%
“…The majority of these studies reported detrimental effects on components of plant fitness, such as reduced shoot and root biomass (Knapp 1986;Quinn and Hall 1996;Wirf 2006), decreased flower, fruit, or seed production (Obeso 1993;Domínguez and Dirzo 1994;Koptur et al 1996;Genter et al 1997), and decreased seed size (Sackston 1959;Rockwood 1973;Koptur et al 1996). On the other hand, some studies have demonstrated compensatory or even beneficial, overcompensatory effects of herbivory (McNaughton 1983;Karban and Myers 1989;Paige 1994;Lennartsson et al 1998;Marshall et al 2005; but see Belsky 1986 andBelsky et al 1993) or variable effects, depending on whether defoliation occurred naturally or was achieved artificially (Gedge and Maun 1992;Nowatzki and Weiss 1997). For example, in wild radish, Raphanus raphanistrum, artificial clipping of leaves by scissors resulted in only minimal induced plant resistance (e.g., increased production of defensive chemicals) (Agrawal 1999(Agrawal , 2000a, whereas strong induced resistance, no induced resistance, or even induced susceptibility to herbivory occurred following attack by four lepidopteran herbivores (Agrawal 2000b).…”
Section: Introductionmentioning
confidence: 94%
“…Another commonly limiting resource for plants is water availability, which might also mediate the ability of species to replace tissues lost to herbivores. A few studies have examined tolerance in relation to water as a limiting resource and the results have been mixed (Georgiadis et al 1989, Nowatzki and Weiss 1997, reviewed in Wise and Abrahamson 2007 and all have focused on withinspecies responses.…”
Section: Resource Availability and Tolerancementioning
confidence: 99%
“…A few studies have examined tolerance in relation to water as a limiting resource and the results have been mixed (Georgiadis et al. , Nowatzki and Weiss , reviewed in Wise and Abrahamson ) and all have focused on within‐species responses.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced tolerance to herbivory in moisture stressed plants has been found previously. Nowatzki and Weiss (1997) showed that feeding impacted canola seedlings more when grown in unstressed conditions compared with seedlings that experienced moisture stress. Similarly, Sun et al (2010) found the weed Alternanthera philoxeroides (Martius) Grisebach, had greater tolerance to herbivores when grown under moisture stress.…”
Section: Discussionmentioning
confidence: 98%